Heteroepitaxial Ge MOS Devices on Si Using Composite AlAs/GaAs Buffer - Peter D. Nguyen; Michael Brian Clavel; Patrick S. Goley; Jheng-Sin Liu; Noah P. Allen; Louis J. Guido; Mantu K. Hudait (IEEE Journal of the Electron Devices Society, 2015)
Structural and electrical characteristics of epitaxial germanium (Ge) heterogeneously integrated on silicon (Si) via a composite, large bandgap AlAs/GaAs buffer are investigated. Electrical characteristics of N-type metal-oxide-semiconductor (MOS) capacitors, fabricated from the aforementioned material stack are then presented. Simulated and experimental X-ray rocking curves show distinct Ge, AlAs, and GaAs epilayer peaks. Moreover, secondary ion mass spectrometry, energy dispersive X-ray spectroscopy (EDS) profile, and EDS line profile suggest limited interdiffusion of the underlying buffer into the Ge layer, which is further indicative of the successful growth of device-quality epitaxial Ge layer. The Ge MOS capacitor devices demonstrated low frequency dispersion of 1.80% per decade, low frequency-dependent flat-band voltage, VFB, shift of 153 mV, efficient Fermi level movement, and limited C-V stretch out. Low interface state density (Dit) from 8.55 × 1011 to 1.09 × 1012 cm-2 eV-1 is indicative of a high-quality oxide/Ge heterointerface, an effective electrical passivation of the Ge surface, and a Ge epitaxy with minimal defects. These superior electrical and material characteristics suggest the feasibility of utilizing large bandgap III-V buffers in the heterointegration of high-mobility channel materials on Si for future high-speed complementary metal-oxide semiconductor logic applications.